1978
DOI: 10.1002/cne.901800109
|View full text |Cite
|
Sign up to set email alerts
|

Radioautographic investigation of gliogenesis in the corpus callosum of young rats II. Origin of microglial cells

Abstract: Microglial cells are absent from the corpus callosum of newborn rats. In the hope of finding out when and how microglial cells appear with age, 3H-thymidine was given intraperitoneally as single or three shortly spaced injections to 5-day-old rats weighing about 15 g; and these animals were sacrificed at various time intervals from 2 hours to 35 days later. Pieces of corpus callosum were taken near the superior lateral angle of the lateral ventricles; and semithin sections were radioautographed and stained wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
91
0
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(103 citation statements)
references
References 48 publications
11
91
0
1
Order By: Relevance
“…Mori and Leblond (1969) suggested that pericytes could be one source of microglia based upon their observation of silver carbonate-stained cells on the capillary wall that resembled microglia in morphology. A number of other investigators have subsequently lent support to this notion (Baron and Gallego, 1972;Brichova, 1972;Sturrock, 1974;Hager, 1975;Boya, 1976), though Imamoto and Leblond (1978) reported they could find no evidence that pericytes migrated into brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Mori and Leblond (1969) suggested that pericytes could be one source of microglia based upon their observation of silver carbonate-stained cells on the capillary wall that resembled microglia in morphology. A number of other investigators have subsequently lent support to this notion (Baron and Gallego, 1972;Brichova, 1972;Sturrock, 1974;Hager, 1975;Boya, 1976), though Imamoto and Leblond (1978) reported they could find no evidence that pericytes migrated into brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The rough endoplasmic reticulum (arrows) is present in single isolated profiles. x 10,500 the hypothesis of the transformation of amoeboid microglia into microglia (Rio-HORTEGA, 1932;KERSHMAN, 1939;IMAMOTO and LEBLOND, 1978;LING, 1981;1MAMOTO et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The small microglial cells described by MORI and LEBLOND (1969) in adult animals, however, are negligible in number or virtually absent during this period as they first appear about the 5th postnatal day (ZING and TAN, 1974;IMAMOTO and LEBLOND, 1978). Soon after their appearance, their number increases steadily with age (ZING and TAN, 1974) so that by weaning age, they form about 5°0 of the total glial population and their total number remains fairly constant thereafter (ZING and LEBLOND,1973).…”
mentioning
confidence: 99%
“…This view was further supported by the discovery that the first appearance of microglial cells coincide with the vascularization of the brain. It was suggested that circulating monocytes enter the nervous system and transform to microglia (Imamoto and Leblond, 1978;Ling, 1979) before the formation of the blood-brain-barrier has been completed (Perry et al, 1985). Infiltration of monocytes could be confirmed by carbon-labelling (Ling et al, 1980) and histochemical studies using marker enzymes for monocytes (Ferrer and Sarmiento, 1980;Ling et al, 1982).…”
Section: Origin and Sources Of Microgliamentioning
confidence: 99%